ANALISA KESESUAIAN LAHAN DAN STRATEGI PENGEMBANGAN BUDIDAYA Gracilaria sp. DI AREA TAMBAK DI KECAMATAN ULUJAMI KABUPATEN PEMALANG - Muhammad Zulfa Zain; Fajar Basuki; Sri Rejeki (Universitas Gadjah Mada, 2012)
The Purpose of this research was (1) to examine the suitability areas of brackish water pond for Gracilaria sp.culture (2) to examine the carrying capacity of brackish water pond for Gracilaria sp.culture development, and (3) to arrange the development strategy of Gracilaria sp.culture in brackish water pond areas. This research was done quantitative descriptively by collecting data. A survey method was applied in this research. The data of Gracilaria sp. culture development at Ulujami District were collected and analysed descriptively by using an area suitability method. The sampling location and respondents were based on a purposive sampling method. The carrying capacity of the total area of the brackish water pond and the Gracilaria sp. total production were analysed both descriptively as well as using SWOT analysis. The results show that based on the area suitability 6,315 Ha or 1% of the total brackish water pond were very suitable (S1) for Gracilaria sp. culture; 605,25 Ha or 99% was suitable and there was no area where was not suitable for Gracilaria sp. culture. However, there was 5,052 Ha brackishwater pond which was very suitable and effective for Gracilaria sp. culture. The Gracilaria sp. yield from those area was 20,208 ton/year. Development strategy of Gracilaria sp. culture at Ulujami district are partner enterprises development, empower comunities organization in economy sector as well as Gracilaria sp. culture technology, technical service in seed selection guidance and postharvest and enterprise management, financials and infrastructures improvement, design of culture areas development, involvement of stakeholders, development of processing home industry and market expansion.